2023
DOI: 10.1186/s13287-023-03325-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the neural stem cells in subventricular zone for the treatment of glioblastoma: an update from preclinical evidence to clinical interventions

Abstract: Background Glioblastoma is one of the most common and aggressive adult brain tumors. The conventional treatment strategy, surgery combined with chemoradiotherapy, did not change the fact that the recurrence rate was high and the survival rate was low. Over the years, accumulating evidence has shown that the subventricular zone has an important role in the recurrence and treatment resistance of glioblastoma. The human adult subventricular zone contains neural stem cells and glioma stem cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Under physiological conditions, neural stem cells (NSCs) differentiate into neuroblasts, then neurons, oligodendrocytes, and astrocytes [ 24 ]. Neuroblasts play a significant role during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, neural stem cells (NSCs) differentiate into neuroblasts, then neurons, oligodendrocytes, and astrocytes [ 24 ]. Neuroblasts play a significant role during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, numerous retrospective studies have confirmed that GBs in close contact with the SVZ possess more aggressive patterns of recurrence and worse clinical outcomes [ 67 , 69 , 70 ]. Therefore, new therapy strategies are being assayed with the aim of targeting SVZ to eradicate NSCs or GSCs [ 71 ].…”
Section: Lessons Learned In the Pathophysiology Of Glioblastomamentioning
confidence: 99%
“…Therefore, comprehensive treatments such as radiotherapy and chemotherapy are often required to prolong patient survival [8,9]. Nevertheless, the recurrence rate remains high after treatment [10]. The average survival time for LGG patients is about ten years, while for HGG patients without treatment, this duration is less than 20 months [11], with only a small fraction of patients surviving more than three years after surgical treatment [12].…”
Section: Introductionmentioning
confidence: 99%